Processing, Microstructure, and Mechanical Behavior of Tungsten Heavy Alloys for Kinetic Energy Penetrators: A Critical Review - Rajneesh Patel; Gangaraju Manogna Karthik; Pawan Sharma (Journal of Manufacturing and Materials Processing)
Tungsten heavy alloys (WHAs) are two-phase composites known for their exceptional density, strength, hardness, and ductility, making them ideal for radiation shielding, kinetic energy penetrators, and aerospace components. Due to their high melting point, WHAs are primarily processed via powder metallurgy, with liquid-phase sintering (LPS). Spark plasma sintering (SPS) and microwave sintering are emerging as advanced consolidation techniques. Recent research has focused on improving WHA performance through microstructural manipulation, alloying with elements like Fe, Co, Mo, and Re; rare earth oxides like Y2O3, La2O3, and Ce2O3; and employing high-entropy alloys (HEAs) as matrix phase. Additionally, additive manufacturing (AM) techniques are increasingly being used to fabricate complex WHA components. Despite their advantages, WHAs still exhibit limitations in penetration performance, primarily due to their tendency to form mushroom-like heads upon impact rather than self-sharpening. Ongoing research seeks to enhance shear localization, refine grain structure, and optimize processing methods to improve the mechanical properties and impact resistance of WHAs. Furthermore, modeling and simulation approaches are being explored to understand the mechanical behavior of WHAs. This review comprehensively overviews the above aspects and presents recent advances in WHA processing.